PROMOTING SAFETY IN CHEMISTRY LABS: BEST PRACTICES AND RISK MANAGEMENT STRATEGIES - Ashoke Hazra (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
Safety in chemistry laboratories is of paramount importance due to the diverse hazards inherent to such environments. This paper examines the precautions necessary for creating a safe laboratory culture. The discussion begins with an overview of potential risks, such as chemical, physical, and fire hazards, and details the essential steps for ensuring safety. Emphasis is placed on personal protective equipment (PPE), proper handling and storage of chemicals, and emergency preparedness. The integration of continuous training and awareness further enhances laboratory safety. By adhering to these principles, we can significantly minimize risks, fostering innovation and learning in a secure environment. Received on: 20/12/2024 Accepted on: 02/01/2025 Published on: 22/01/2025